Living with animals : bonds across species - Porter, Natalie (Natalie H.); Gershon, Ilana; Musharbash, Yasmine (Cornell University Press, 2018)
Living with Animals is a collection of imagined animal guides--a playful and accessible look at different human-animal relationships around the world. Anthropologists and their co-authors have written accounts of how humans and animals interact in labs, in farms, in zoos, and in African forests, among other places. Modeled after the classic A World of Babies, an edited collection of imagined Dr. Spock manuals from around the world--With Animals focuses on human-animal relationships in their myriad forms. This is ethnographic fiction for those curious about how animals are used for a variety of different tasks around the world. To be sure, animal guides are not a universal genre, so Living with Animals offers an imaginative solution, doing justice to the ways details about animals are conveyed in culturally specific ways by adopting a range of voices and perspectives. How we capitalize on animals, how we live with them, and how humans attempt to control the untamable nature around them are all considered by the authors of this wild read. If you have ever experienced a moment of "what if" curiosity--what is it like to be a gorilla in a zoo, to work in a pig factory farm, to breed cows and horses, this book is for you. A light-handed and light-hearted approach to a fascinating and nuanced subject, Living with Animals suggests many ways in which we can and do coexist with our non-human partners on Earth.